At the Crossroad Between Resiliency and Fragility: A Neurodevelopmental Perspective on Early-Life Experiences - Chelini, Gabriele; Pangrazzi, Luca; Bozzi, Yuri (Frontiers in Cellular Neuroscience, 2022)
Brain postnatal development is characterized by sensitive windows where local circuitry is drastically reshaped by life experiences. These phases, known as critical periods, occur at different time points for different brain functions, presenting redundant physiological changes in the underlying brain regions. While circuits malleability during critical periods provides a valuable window of opportunity for adaptive fine-tuning to the living environment, this aspect of neurodevelopment also represents a phase of increased vulnerability for the development of a variety of disorders. Consistently, accumulating epidemiological studies point to adverse childhood experience as a major risk factor for many medical conditions, especially stress- and anxiety-related conditions. Thanks to creative approaches to manipulate rodents’ rearing environment, neurobiologist have uncovered a pivotal interaction between critical periods and early-life experiences, offering an interesting landscape to improve our understanding of brain disorders. In this short review, we discuss how early-life experience impacts cellular and molecular players contributing to critical periods of development, translating into long-lasting behavioral consequences in rodents. Bundling together findings from multiple laboratories, we delineate a unifying theory where systemic factors dynamically target the maturation of brain functions based on adaptive needs, shifting the balance between resilience and vulnerability in response to the quality of the rearing environment.